Impact of an Interdisciplinary Experience in Developing Story Writing Skills in the History Classroom from the A + S Methodology - Valdés León, Gabriel (2019)
The work presented here gives account of the results obtained after the implementation of a Service Learning Project that UCSH carried out together with the municipal school Los Bosquinos de Maipú. The main objective of this work was to evaluate the impact of this experience in the development of the production of narrative texts in the classroom of History, Geography and Social Science through an interdisciplinary work. From a didactic perspective, a didactic module was developed that is based on writing by projects from a processual approach. The study, of pre-experimental type with quantitative analysis, considers the textual revision, on the part of three expert judges, of the stories made by 32 students of seventh grade. The results show a considerable improvement in the quality of narrative texts, with an emphasis on discursive competence. On the other hand, the value that this experience of Service Learning represented not only for the institution of higher education, but also for the community partner stands out.